Lanthanides Toxicity in Zebrafish Embryos Are Correlated to Their Atomic Number - Lin, Ying-Ting; Liu, Rong-Xuan; Audira, Gilbert; Suryanto, Michael Edbert; Roldan, Marri Jmelou M.; Lee, Jiann-Shing; Ger, Tzong-Rong; Hsiao, Chung-Der (Toxics (Basel), 2022)
Rare earth elements (REEs) are critical metallic materials with a broad application in industry and biomedicine. The exponential increase in REEs utilization might elevate the toxicity to aquatic animals if they are released into the water due to uncareful handling. The specific objective of our study is to explore comprehensively the critical factor of a model Lanthanide complex electronic structures for the acute toxicity of REEs based on utilizing zebrafish as a model animal. Based on the 96 h LC50 test, we found that the majority of light REEs display lower LC50 values (4.19–25.17 ppm) than heavy REEs (10.30–41.83 ppm); indicating that they are atomic number dependent. Later, linear regression analyses further show that the average carbon charge on the aromatic ring (aromatic Cavg charge) can be the most significant electronic structural factor responsible for the Lanthanides’ toxicity in zebrafish embryos. Our results confirm a very strong correlation of LC50 to Lanthanide’s atomic numbers (r = 0.72), Milliken charge (r = 0.70), and aromatic Cavg charge (r = −0.85). This most significant correlation suggests a possible toxicity mechanism that the Lanthanide cation’s capability to stably bind to the aromatic ring on the residue of targeted proteins via a covalent chelating bond. Instead, the increasing ionic bond character can reduce REEs’ toxicity. In addition, Lanthanide toxicity was also evaluated by observing the disruption of photo motor response (PMR) activity in zebrafish embryos. Our study provides the first in vivo evidence to demonstrate the correlation between an atomic number of Lanthanide ions and the Lanthanide toxicity to zebrafish embryos.